Trajetórias biográficas: o habitus leitor de professoras em Teresina-PI - Gondinho, Marta Rochelly Ribeiro (2010)
This is a research about the reading habitus of teachers developed along their biographic trajectory. The research has a qualitative aspect, which proposed to analyze the constitution of the reading habitus of teachers of the public and private teaching board of Teresina – Piauí. Under the questioning on how the reading habitus was constituted, it was searched to understand which was the relation between the cultural capital and the reader trajectory of teachers. It was supported by the Sociology of Pierre Bourdieu (1992, 1994, 1998, 2007), about the concept of cultural capital, habitus and the contributions of Praxiology. It was still used the proposal of the Sociology of reading of Bernard Lahire (1997,2002, 2005,2006) about the concept of dispositions, socializating experiences and dissonance, also in the cultural history recommended by Roger Chartier (2002), about the reading as a cultural historicized practice. To constitute the trajectories, it was made narrating interviews by the methodology of the oral history and by the investigative approach of the history of life. For the appropriation of the profile of the subjects, it was applied a questionnaire to four interviewed teachers. The constitution of the trajectories permitted to revel the experiences of reading and its relation with the incorporation of the dispositions, giving support to understand that there are direct implications of the acquisition of the cultural capital in the formation of the reader. It was also possible to detach that the meaning of the reading to the reader is built through his/her social and cultural practice, continuously proportioned by socializating activities, deconstructing in some cases the idea of reproduction, emphasizing the out of tune voices, therefore fitting new meanings for the concept of cultural capital. In final considerations, this research stimulated the moving of the reading formation to the reader in its singularities identifying the place of the cultural experiences in such formation.